MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA KELAS IV SD - Lestari, Hana; Fauziah, Alma; Amaliyah, Pirda (Institut Agama Islam Sahid (INAIS) Bogor, 2024)
Problem-based learning (PBL) is a pedagogical approach that situates students at the centre of the learning process, confronting them with authentic problems and challenges, with the aim of fostering their capacity to solve these problems effectively. The process of problem-based learning (PBL) presents students with a real-world problem, thereby facilitating the development of conceptual understanding. The objective of this research is to ascertain how the PBL model can be effectively employed to enhance students' conceptual understanding. The methodology employed is a pre-experimental one, utilising a one-group pretest-posttest research design. The research was conducted at SDN Cemplang 4, Bogor Regency. The study sample consisted of 31 students, comprising 16 boys and 15 girls. The instruments employed were concept understanding test questions and observation sheets. The concept understanding ability test was conducted in two stages: the pretest and the posttest. The results of the study indicate that students demonstrated an average understanding of the concept in question of 62.81 on the pretest and 83.0 on the posttest. The data were analysed using the Statistical Package for the Social Sciences (SPSS) version 21 for Windows with a Paired Sample t-test at the 5% significance level, which yielded a significance value of 0.000, less than the 5% level. This indicates that there was a statistically significant difference between the pretest and posttest results. Moreover, the N-gain value (medium category) is 0.498, indicating that students' ability to comprehend the concept has improved from the pretest to the posttest.